Microcephalic primordial dwarfism in an Emirati patient with PNKP mutation. Issue 8 (27th May 2016) - Nair, Pratibha; Hamzeh, Abdul Rezzak; Mohamed, Madiha; Saif, Fatima; Tawfiq, Nafisa; El Halik, Majdi; Al‐Ali, Mahmoud Taleb; Bastaki, Fatma
Abstract : Microcephaly is a rare neurological condition, both in isolation and when it occurs as part of a syndrome. One of the syndromic forms of microcephaly is microcephaly, seizures and developmental delay (MCSZ) (OMIM #613402), a rare autosomal recessive neurodevelopmental disorder with a range of phenotypic severity, and known to be caused by mutations in the polynucleotide kinase 3′ phosphatase ( PNKP) gene. The PNK protein is a key enzyme involved in the repair of single and double stranded DNA breaks, a process which is particularly important in the nervous system. We describe an Emirati patient who presented with microcephaly, short stature, uncontrollable tonic‐clonic seizures, facial dysmorphism, and developmental delay, while at the same time showing evidence of brain atrophy and agenesis of the corpus callosum. We used whole exome sequencing to identify homozygosity for a missense c.1385G > C (p.Arg462Pro) mutation in PNKP in the patient and heterozygosity for this mutation in her consanguineous parents. The Arg 462 residue forms a part of the lid subdomain helix of the P‐loop Kinase domain. Although our patient's phenotype resembled that of MCSZ, the short stature and evidence of brain atrophy distinguished it from other classic cases of the condition. The report raises the question of whether to consider this case as an atypical variant of MCSZ or as a novel form of microcephalic primordial dwarfism. © 2016 Wiley Periodicals, Inc.